2022
DOI: 10.3389/fonc.2022.830003
|View full text |Cite
|
Sign up to set email alerts
|

Rare Primary Adrenal Tumor: A Case Report of Teratomas and Literatures Review

Abstract: Teratomas are very rare, originating from embryonal germ layers. The majority of them are mature, most common in the gonads, and with only 15% out of gonads. In particular, primary adrenal teratomas are extremely rare. The present study reported a case of a young female patient with right adrenal tumor who underwent intermittent pain in the right waist and abdomen and whose CT of adrenal gland showed an 88 mm × 79 mm × 69 mm mass. Besides, her adrenal gland-related hormones are not abnormal. Laparoscopic adren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Ectopic thyroid tissue may have originally existed, and part of it may have acquired an unknown driver alteration. Primary adrenal teratomas are rare, with only 49 cases reported [ 26 ]. While only a few studies have detailed its histology, multiple layers of embryonic germ cells have been observed, and there has been no description of a monodermal teratoma containing only thyroid tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic thyroid tissue may have originally existed, and part of it may have acquired an unknown driver alteration. Primary adrenal teratomas are rare, with only 49 cases reported [ 26 ]. While only a few studies have detailed its histology, multiple layers of embryonic germ cells have been observed, and there has been no description of a monodermal teratoma containing only thyroid tissue.…”
Section: Discussionmentioning
confidence: 99%